Avaliação do uso da ultrassonografia epiaórtica na identificação de doença aterosclerótica da aorta ascendente e seu impacto sobre a estratégia operatória em pacientes submetidos a cirurgias cardiovasculares. - Gondim, Aloísio Sales Barbosa (2024)
Introduction: Atherosclerosis affects the most varied arterial segments of the cardiovascular system and is characterized by the formation of atheromatous plaques formed by modified lipids and varying degrees of calcification. The presence of atherosclerosis of the ascending thoracic aorta is an important risk factor for perioperative stroke and systemic atheroembolism in individuals undergoing cardiovascular procedures. Objectives: This study aimed to evaluate the use of epiaortic ultrasound (EAU) and compare it to digital palpation in identifying atherosclerotic disease of the ascending thoracic aorta (ATA) and its impact on the operative strategy adopted in individuals undergoing cardiovascular surgery. Methods: Prospective, analytical, experimental study that evaluated the use of UEA, combined with digital palpation and transesophageal echocardiography, in identifying atherosclerotic disease of the ascending aorta in participating individuals who underwent cardiovascular surgery at HUWC. Once the epiaortic examination and digital palpation of the ascending thoracic aorta (ATA) had been carried out, after discussion between the surgeons about the results, a change in the management of the ATA was taken. After collection, the data reported in a specific form were entered into EPIINFO and analyzed in the SPSS 26.0 software for Windows® for subsequent statistical analysis. Results: Nineteen participants met study inclusion criteria and agreed to participate. Among the participants, 14 patients were identified as having atherosclerotic disease of the ascending aorta (73%) through UEA. Six participants who had moderate and/or severe plaques had their surgical strategy modified (31.5%). In these six participants, the UEA showed anterior atheroma in the proximal and middle segments in 4 individuals and anterior distal atheroma in 6 patients. Digital palpation, among the individuals who had their surgery modified, identified only one patient with anterior involvement of the aorta in its proximal and distal thirds (17%). Conclusion: Analysis with epiaortic ultrasound allowed the identification of atherosclerotic disease of the ATA that was not diagnosed by digital palpation and TEE. UEA was more sensitive compared to both palpation and transesophageal echocardiography in diagnosing atheroma in the proximal, middle, and distal segments of the ascending thoracic aorta.